Implicit large eddy simulation of the flow past NACA0012 aerofoil at a Reynolds number of 1x10^5 - Li, Zhuoneng; Rana, Zeeshan A. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
In this paper, the implicit Large Eddy Simulation (iLES) incorporating an unstructured 3rd-order Weighted Essential Non-Oscillatory (WENO) reconstruction method is investigated on the flow past NACA0012 aerofoil at a Reynolds number of 1 × 10^5. The flow features involve laminar separation, transition to turbulent and re-attachment. Simulations are carried out in the framework of open-source package OpenFOAM with a 2nd-order Euler implicit time integration and Pressure-Implicit Splitting-Operator (PISO) algorithm is used for the pressure-velocity coupling. Conventional LES with Wall Adapting Local Eddy Viscosity (WALE) model is also carried out as a baseline. The results are compared with Direct Numerical Simulations (DNS) under the same flow configurations. The mean quantities such as pressure coefficient and the re-attached turbulent velocity profiles are in excellent agreement with the DNS reference. On the other hand, in the transitional region, the thickness of separation bubble obtained by both iLES and LES is thinner than the DNS. The current iLES approach has achieved a 35% reduction of mesh resolution compared to wall resolving LES and 70% reduction compared to DNS, while the accuracy is mostly satisfied.
Keywords: Aerodynamic Characteristics; NACA 0012; Implicit Large Eddy Simulation; Flow Characteristics; Kelvin Helmholtz Instability; Wall Adapting Local Eddy Viscosity; Boundary Layer Separation; Skin Friction Coefficient; Incompressible Flow; Angle of Attack